2020
DOI: 10.1002/app.50004
|View full text |Cite
|
Sign up to set email alerts
|

High‐viscoelastic graft modified chitosan hydrophobic association polymer for enhanced oil recovery

Abstract: The conventional partially hydrolyzed polyacrylamide (HPAM) is greatly restricted by its single linear molecular structure in oil reservoirs with severe reservoir conditions such as high temperature and high salt. In this article, the chitosan (CS) grafted imidazoline monomer copolymer (CS-g-AM/AA/NIDA) was prepared from N-maleyl CS (N-MCS), acrylamide (AM), acrylic acid (AA), 1-(2-N-acryloylaminoethyl)-2-oleoyl imidazoline (NIDA) by free radical copolymerization. The structure was determined by means of Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, when the concentration of polymer solution is higher than critical association concentration, hydrophobic groups will have the tendency to form a transient reversible three-dimensional supramolecular network structure, which will make HAP have good thickening characteristics under high-temperature and high-salt conditions [3]. Due to the above characteristics, HAP is widely used in the field of oil development, such as hydraulic fracturing fluid preparation [4][5][6] and polymer flooding [7][8][9][10]. In this paper, HAP was selected to fit the high-temperature and high-salt condition of the Bohai Oilfield reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the concentration of polymer solution is higher than critical association concentration, hydrophobic groups will have the tendency to form a transient reversible three-dimensional supramolecular network structure, which will make HAP have good thickening characteristics under high-temperature and high-salt conditions [3]. Due to the above characteristics, HAP is widely used in the field of oil development, such as hydraulic fracturing fluid preparation [4][5][6] and polymer flooding [7][8][9][10]. In this paper, HAP was selected to fit the high-temperature and high-salt condition of the Bohai Oilfield reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Francisco 33 synthesized trimethyl chitosan and trimethyl chitosan hydrophobized with myristoyl chloride and confirmed that they have an excellent ability to enhance the recovery of carbonate reservoirs. Liu 34 synthesized the chitosan grafted imidazoline monomer copolymer, and the core flooding experiments showed that oil recovery could improve up to 8.08%.…”
Section: Introductionmentioning
confidence: 99%